Pesan Moral dalam Puisi “Padamu Jua” Karya Amir Hamzah - Akhsin Ridho (Madah: Jurnal Bahasa dan Sastra, 2019)
The shift in the values of life in a society increasingly fades and is inevitable from other cultural influences especially for students who are in transition looking for their identity. This create problem for the community itself and in the end, the traditional values were neglected. Such problems can actually be minimized if we can learn from history. Therefore, this research was conducted by reading and interpreting the poem "Padamu Jua" by Amir Hamzah by using a hermeneutic approach. The renewal lies in the method approach used in analyzing each paragraph of poetry by looking at and exploring the history of the author. Interpretation is conducted through a literature review of the life journey of Amir Hamzah at the time of writing the poem. The results of the research of hermeneutics in the poetry text can be concluded to tell about the inner upheaval between tradition and the principle of life. The meaning of this poem can be a lesson (advice) for everyone, especially for those who are learning to be careful, not wrong in making decisions. Each region has its own traditions and culture that cannot be violated by the community. Situations, upheaval, and feelings kept in the heart may not change the sense of compliance with parents.